2011
DOI: 10.1002/mc.21833
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor signals regulate UDP‐glucuronosyltransferases in the urinary bladder: A potential mechanism of androgen‐induced bladder carcinogenesis

Abstract: UDP-glucuronosyltransferases (UGTs), major phase II drug metabolism enzymes, play an important role in urinary bladder cancer initiation by detoxifying carcinogens. We aimed to determine if androgens regulate UGT expression via the androgen receptor (AR) pathway in the bladder. Real-time reverse transcription-polymerase chain reaction and Western blot analyses were used to assess UGT1A levels in the normal urothelium SVHUC cell line stably expressed with AR and in bladder tissues from AR knockout (ARKO) and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 38 publications
2
91
0
2
Order By: Relevance
“…Interestingly, the UGT1A gene cluster has been identified as a novel susceptibility locus for bladder cancer using genome-wide association studies (38). Furthermore, experimental evidence has shown that UGT1A expression becomes downregulated during bladder cancer progression in animal models (39), consistent with the hypothesis that UGT variants mapping to this region may provide a protective, tumor-suppressive function in bladder cells (40). FGFR3 fusion protein expression is likely to be an important biomarker to aid in patient selection when evaluating novel bladder cancer treatments, due to an increased susceptibility of fusion-bearing tumor cells to targeted FGFR therapies (9).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the UGT1A gene cluster has been identified as a novel susceptibility locus for bladder cancer using genome-wide association studies (38). Furthermore, experimental evidence has shown that UGT1A expression becomes downregulated during bladder cancer progression in animal models (39), consistent with the hypothesis that UGT variants mapping to this region may provide a protective, tumor-suppressive function in bladder cells (40). FGFR3 fusion protein expression is likely to be an important biomarker to aid in patient selection when evaluating novel bladder cancer treatments, due to an increased susceptibility of fusion-bearing tumor cells to targeted FGFR therapies (9).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was then performed in 15 μl system by using SYBR GreenER qPCR SuperMix for iCycler (Invitrogen), as described previously. 31,38 The primer sequences are given as below: GATA3 (forward, 5′-CAGCCTTCGC TTGGGCTTAA T-3′; reverse, 5′-GATGGCAGGC TCAGTGATGT C-3′), VEGF (forward, 5′-CTGTACCTCC ACCATGCCAA G-3′; reverse, 5′-GGTACTCCTG GAAGATGTCC ACC-3′), MMP-2 (forward, 5′-TACAGGATCA TTGGCTACAC ACC-3′; reverse, 5′-GGTCACATCG CTCCAGACT-3′), and MMP-9 (forward, 5′-TGTACCGCTA TGGTTACACT CG-3′; reverse, 5′-GGCAGGGACA GTTGCTTCT-3′). GAPDH (forward, 5′-AAGGTGAAGG TCGGAGTCAA C-3′; reverse, 5′-GGGGTCATTG ATGGCAACAA TA-3′) was used as an internal control.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Bladder tissue microarray (TMA) was constructed from 24 formalin-fixed paraffin-embedded cystectomy specimens retrieved from the Surgical Pathology archives, as described previously (Zheng et al 2011, Izumi et al 2013. Appropriate approval from the Institutional Review Board of the University of Rochester Medical Center was obtained before construction and use of the TMA.…”
Section: Bladder Tissue Microarray and Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining was performed on the sections (5 mm thick) from the bladder TMA, as described previously (Zheng et al 2011, Izumi et al 2013, with minor modifications. Briefly, tissues were deparaffinized in xylene, rehydrated in a graded ethanol series, and incubated in 3% hydrogen peroxide to block endogenous peroxidase.…”
Section: Bladder Tissue Microarray and Immunohistochemistrymentioning
confidence: 99%